Metal lithium negative electrode active material and preparation method thereof, metal lithium negative electrode and metal lithium battery
By using Fe2O3-carbon composite materials containing nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles in metal lithium batteries, the problems of poor lithium deposition uniformity and poor circulation performance during charging and discharge of metal lithium batteries are solved, and higher cycle stability and safety are achieved.
Patent Information
- Application Number
- CN202311214193.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-19
- Publication Date
- 2025-03-21
AI Technical Summary
During the charging and discharging process, metal lithium batteries have problems such as poor lithium deposition uniformity and poor circulation performance, and it is easy to lead to safety hazards and thermal runaway.
Using a negative electrode active material including metal lithium and Fe2O3-carbon composite, the Fe2O3-carbon composite consists of nitrogen and oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled inside the cage, metal lithium is deposited by electrodeposition method.
The cycle stability, specific capacity and Coulomb efficiency of the metal lithium negative electrode are improved, the growth of lithium dendrites is inhibited, and the safety of the battery is enhanced.
Smart Images

Figure CN119674070A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of metal lithium batteries, and in particular to a metal lithium negative electrode active material and a preparation method thereof, a metal lithium negative electrode and a metal lithium battery. Background Art
[0002] In recent years, lithium metal anodes have received extensive attention from battery researchers due to the characteristics of lithium metal such as high theoretical specific capacity and low electrode potential. However, there are also many problems. On the one hand, due to the high reactivity of lithium metal, it is easy to react with organic electrolytes, and a large amount of gas will be produced, which will lead to a decrease in the utilization rate of lithium metal and electrolyte, and it is easy to bring safety hazards. Secondly, after multiple charge and discharge of the battery, lithium dendrites will continue to grow on the surface of lithium metal. A large number of dendrites have a large stress on the diaphragm, causing the diaphragm to be pierced, thereby causing thermal runaway of the battery. In addition, the unlimited volume expansion of lithium metal will also lead to various problems such as lithium electrode pulverization, electrolyte consumption, and large-scale gas production. These problems make it difficult for lithium metal anodes to be commercially applied.
[0003] In order to solve the above problems, the main technical routes adopted in the prior art include: developing modified electrolytes, negative electrode surface passivation modification, and developing composite negative electrode materials. However, the methods of modified electrolytes and negative electrode surface passivation modification are often only applicable to battery systems with specific electrolytes and positive and negative electrodes. At the same time, the process is cumbersome and the cost is high. In the development of composite negative electrode materials, three-dimensional nanomaterials with a certain strength and stable structure are used as current collectors to form composite negative electrodes with metallic lithium. However, the carbon nanonetworks that are currently widely studied have poor lithium affinity, and metallic lithium is deposited on the surface, so that lithium is still in an exposed state, which is easy to react with the electrolyte, and the effect is not good in practical applications. Summary of the invention
[0004] The purpose of the present invention is to overcome the problems of poor lithium deposition uniformity and poor cycle performance in the charge and discharge process of metal lithium batteries in the prior art, and to provide a metal lithium negative electrode active material and a preparation method thereof, a metal lithium negative electrode and a metal lithium battery. The metal lithium negative electrode active material is used in a metal lithium battery and has excellent cycle stability.
[0005] In order to achieve the above-mentioned object, the present invention provides a metal lithium negative electrode active material on the one hand, wherein the negative electrode active material comprises metal lithium and a Fe2O3-carbon composite material;
[0006] Wherein, the Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages;
[0007] The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
[0008] A second aspect of the present invention provides a method for preparing a metallic lithium negative electrode active material, the preparation method comprising: depositing metallic lithium into a Fe2O3-carbon composite material by electrodeposition;
[0009] The Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages;
[0010] The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
[0011] The third aspect of the present invention provides a metallic lithium negative electrode, which includes a current collector and an active layer composited on the current collector, and the active layer includes the metallic lithium negative electrode active material described in the first aspect or the metallic lithium negative electrode active material prepared by the preparation method described in the second aspect.
[0012] A fourth aspect of the present invention provides a metal lithium battery, wherein the metal lithium battery comprises the metal lithium negative electrode described in the third aspect.
[0013] The lithium metal battery negative electrode active material provided by the present invention comprises metal lithium and Fe2O3-carbon composite material, wherein the Fe2O3-carbon composite material adopts nitrogen-oxygen co-doped carbon nano cage as a carrier, and the carbon cage is loaded with Fe2O3 nanoparticles, which has good lithium affinity, is conducive to reducing the nucleation overpotential of metal lithium, is conducive to inducing metal lithium to enter the carbon nano cage for deposition, and effectively inhibits the growth of metal lithium dendrites during charging and discharging. When applied to metal lithium batteries, it can effectively improve the specific capacity, cycle performance and coulombic efficiency of the metal lithium negative electrode. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] Figure 1 is a TEM image of the Fe2O3-carbon composite material in Preparation Example 1;
[0015] Figure 2 is the XPS graph of the Fe2O3-carbon composite material in Preparation Example 1;
[0016] Figure 3 is the XPS Fe 2p spectrum of the Fe2O3-carbon composite material prepared in Preparation Example 1;
[0017] Figure 4 is a SEM image of the negative electrode active material prepared in Example 1 after cycling. DETAILED DESCRIPTION
[0018] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0019] A first aspect of the present invention provides a metallic lithium negative electrode active material, the negative electrode active material comprising metallic lithium and a Fe2O3-carbon composite material;
[0020] Wherein, the Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages;
[0021] The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
[0022] In the present invention, the nitrogen-oxygen co-doped carbon nanocage has a hollow cage structure surrounded by nitrogen-oxygen co-doped graphitized carbon layers, and the graphitized carbon layer refers to a carbon structure with a layered structure that can be clearly observed under a high-resolution transmission electron microscope, rather than an amorphous structure.
[0023] In the present invention, the "nitrogen" and "oxygen" in the term "nitrogen-oxygen co-doped carbon nanocage" refer to nitrogen and oxygen elements, that is, nitrogen and oxygen elements in various forms formed in the graphitized carbon layer during the preparation of nitrogen-oxygen co-doped carbon nanocages. The "molar content of oxygen" is the total content of all forms of oxygen elements, and similarly, the "molar content of nitrogen" is the total content of all forms of nitrogen elements.
[0024] Transmission electron microscopy (TEM) characterization shows that the composite material has a cage-like structure, and clear Fe2O3 lattice fringes can be seen in the cage, proving that Fe2O3 is contained in the carbon cage. At the same time, through X-ray photoelectron spectroscopy analysis and XRD testing, it can be determined that the iron element in the composite material exists in the form of Fe2O3.
[0025] According to some preferred embodiments of the present invention, the molar content of carbon in the Fe2O3-carbon composite material is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5% as measured by X-ray photoelectron spectroscopy. It is understood that when the composite material contains only carbon, oxygen, nitrogen and iron elements, the sum of the molar contents of each component satisfies 100%.
[0026] In the present invention, the X-ray photoelectron spectroscopy analysis was tested on an ESCALab250 X-ray photoelectron spectrometer equipped with ThermoAvantage V5.926 software from Thermo Scientific. The excitation source was monochromatic AlKα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis test was 6.53×10 -9 The electron binding energy was calibrated with the C1s peak (284.6 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.
[0027] In the present invention, preferably, the molar ratio of oxygen to nitrogen in the composite material measured by X-ray photoelectron spectroscopy is 5-15:1, for example, it can be any one of 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1 or a ratio between two points. By controlling the ratio of nitrogen and oxygen co-doping, it is more conducive to inhibiting the growth of metal lithium dendrites and improving the cycle performance of metal lithium batteries. Preferably, the molar ratio of oxygen to nitrogen is 5-10:1.
[0028] According to some preferred embodiments of the present invention, based on the total amount of the negative electrode active material, the content of metallic lithium is 5-50wt%, preferably 10-30wt%, and the content of the Fe2O3-carbon composite material is 50-95wt%, preferably 70-90wt%.
[0029] According to the present invention, preferably, the metal lithium is compounded with the Fe2O3-carbon composite material by an electrodeposition method, so that the metal lithium is filled in the cage cavity of the nitrogen-oxygen co-doped carbon nanocage. In the above preferred case, it is beneficial to further improve the cycle performance of the metal lithium negative electrode active material.
[0030] According to the present invention, preferably, the particle diameter of the Fe2O3-carbon composite material is 5-40nm, preferably 5-30nm, and more preferably 5-20nm. The particles of the Fe2O3-carbon composite material have a small diameter and a large curvature, which is conducive to the transmission and deposition of metallic lithium.
[0031] Preferably, the thickness of the cage wall of the nitrogen and oxygen co-doped carbon nanocage in the Fe2O3-carbon composite material is 1-30 nm, preferably 1-10 nm, and more preferably 1-5 nm.
[0032] In the present invention, the surface morphology of the Fe2O3-carbon composite material is characterized by high-resolution transmission electron microscopy (HRTEM), the model of the high-resolution transmission electron microscope used is JEM-2100 (Japan Electron Co., Ltd.), and the high-resolution transmission electron microscope test conditions are: the acceleration voltage is 200kV. The diameter of the nitrogen-oxygen co-doped carbon nanocage and the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage can be measured by high-resolution transmission electron microscope images.
[0033] According to the present invention, preferably, the specific surface area of the nitrogen and oxygen co-doped carbon nanocage is 50-1000m 2 / g, preferably 200-800m 2 / g, more preferably 300-600m 2 / g.
[0034] According to the present invention, the nitrogen-oxygen co-doped carbon nanocage has a loose and porous cage wall, which is conducive to the filling and deposition of metallic lithium. Preferably, the pore volume of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 0.5-1cm 3 / g, preferably 0.65-1cm 3 / g.
[0035] In the present invention, the pore structure properties of the material are detected by the BET test method, which is specifically measured using a Quantachrome AS-6B analyzer, and the BET specific surface area of the material is obtained by the Brunauer-Emmett-Taller (BET) method.
[0036] A second aspect of the present invention provides a method for preparing a metallic lithium negative electrode active material, the preparation method comprising: depositing metallic lithium into a Fe2O3-carbon composite material by electrodeposition;
[0037] The Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages;
[0038] The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
[0039] In the invention, there is no particular requirement for the specific method of the electrodeposition, and the electrodeposition method conventional in the art can be used. Preferably, the electrodeposition is selected from constant direct current electrodeposition and / or pulse electrodeposition.
[0040] The present invention has no particular limitation on the specific conditions of the constant direct current electrodeposition and / or pulse electrodeposition, and can be carried out under conventional operating conditions in the art. The Fe2O3-carbon composite material can be used as the negative electrode material, and lithium can be used as the counter electrode to assemble into a half-cell, and then electrodeposition can be carried out. The present invention has no particular requirements on the composition and structure of the half-cell, as long as the deposition amount of metallic lithium can be met. Preferably, the electrodeposition is constant direct current electrodeposition, and the current of the constant direct current electrodeposition can be 0.5-5 mA / cm 2 .
[0041] Preferably, the electrodeposition is such that, based on the total amount of the negative electrode active material obtained, the content of metallic lithium is 5-50wt%, preferably 10-30wt%, and the content of the Fe2O3-carbon composite material is 50-95wt%, preferably 70-90wt%.
[0042] The composition and structure of the Fe2O3-carbon composite material are within the same definition as described in the first aspect and will not be repeated here.
[0043] According to some preferred embodiments of the present invention, the method for preparing the Fe2O3-carbon composite material comprises:
[0044] (1) providing a homogeneous solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.1-100;
[0045] (2) subjecting the precursor to low-temperature pyrolysis in an inert atmosphere and / or a reducing atmosphere to obtain a pyrolysis product; the temperature of the low-temperature pyrolysis is not higher than 650° C.;
[0046] (3) acid-washing the pyrolysis product, and then performing solid-liquid separation, washing and drying to obtain nitrogen-oxygen co-doped carbon nanocages;
[0047] (4) Under vacuum conditions, impregnating the nitrogen-oxygen co-doped carbon nanocage with an iron salt solution, and then performing a heat treatment;
[0048] (5) Under an oxygen-containing atmosphere, the product obtained in step (4) is passivated.
[0049] In the above preferred embodiment, a nitrogen-oxygen co-doped carbon nano cage carrier is first prepared, and then a metal oxide is introduced into the carrier by vacuum impregnation. The precursor obtained by reacting a transition metal salt and a nitrogen-containing organic carboxylic acid in a solvent is pyrolyzed at a relatively low temperature, and then the nitrogen-oxygen co-doped carbon nano cage is obtained by acid washing. The obtained nitrogen-oxygen co-doped carbon nano cage has a relatively high oxygen content. The above preferred preparation method overcomes the problems of the prior art that the metal organic framework structure precursor needs to be self-assembled using a high-temperature and high-pressure reactor, a large amount of organic solvent is wasted, and the purification steps are cumbersome, and no polymer additives are required, the reaction steps are simplified, and no exogenous templates need to be introduced, which is conducive to large-scale production and has low cost.
[0050] According to some preferred embodiments of the present invention, the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.5-50, preferably 1:0.5-5.
[0051] The present invention has no particular limitation on the specific method of forming the homogeneous solution in step (1), for example, the homogeneous solution may be formed by heating, preferably by heating and stirring. The present invention also has no particular limitation on the heating temperature and stirring rate, as long as the homogeneous solution can be formed.
[0052] According to the present invention, preferably, the transition metal salt and the nitrogen-containing organic carboxylic acid are dissolved in a solvent to form a homogeneous solution. The present invention has no particular limitation on the type of the solvent, as long as a homogeneous solution can be formed. Preferably, the solvent is water and / or ethanol, more preferably water; the present invention has no particular limitation on the amount of the solvent, as long as a homogeneous solution can be formed.
[0053] In the present invention, the solvent in the homogeneous solution can be removed by existing techniques known to those skilled in the art, and the present invention has no particular limitation on this. For example, the solvent in the homogeneous solution can be removed by heating and evaporating to dryness.
[0054] In the present invention, there is no special limitation on the specific type of the transition metal salt. Preferably, the transition metal salt is selected from organic acid salts and / or inorganic salts of transition metals; preferably, the organic acid salt of the transition metal is an organic carboxylate free of heteroatoms, preferably acetate; preferably, the inorganic salt of the transition metal is at least one of transition metal halides, carbonates and basic carbonates.
[0055] In the present invention, preferably, the transition metal is a Group VIII metal and / or a Group IB metal, preferably at least one of iron, cobalt, nickel and copper, more preferably nickel.
[0056] According to the present invention, preferably, in step (2), the low-temperature pyrolysis conditions include: a heating rate of 0.5-30°C / min, preferably 1-10°C / min; a temperature of 350-450°C, preferably 350-400°C; for example, it can be a specific temperature of 350°C, 360°C, 370°C, 380°C, 390°C, 400°C, or a temperature range between two points. Preferably, the constant temperature time is 20-600min, preferably 60-480min. In the prior art, in order to ensure that the carbon coating has a high degree of graphitization, the calcination or heat treatment temperature generally used is not less than 600°C. A high degree of graphitization is conducive to improving the conductivity of the material. However, the inventors of the present invention have found in their research that a lower calcination temperature can increase the oxygen content in the material, and the metal lithium negative electrode active material further prepared has stable cycle performance and higher charge and discharge efficiency.
[0057] In the present invention, preferably, in step (2), the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium.
[0058] Preferably, the reducing atmosphere is hydrogen.
[0059] In the present invention, in step (3), the acid washing peels off the transition metal to form a hollow cage-like structure. The specific operation process of the acid washing can adopt the existing technology known to those skilled in the art, and the present invention has no special limitation on this.
[0060] Preferably, the pickling comprises: mixing the pyrolysis product with a pickling agent. The present invention has no particular limitation on the specific manner of the mixing, and the mixing can be performed by ultrasound or stirring.
[0061] The pickling agent can be an acid or an acid aqueous solution conventional in the art. As long as the transition metal can be stripped. Preferably, the pickling agent is an inorganic acid aqueous solution and / or an organic acid aqueous solution, preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution and a citric acid aqueous solution, more preferably a hydrochloric acid aqueous solution. Preferably, the concentration of the inorganic acid aqueous solution or the organic acid aqueous solution is 0.5-2 mol / L. The present invention does not particularly limit the amount of the pickling agent, as long as the transition metal can be stripped, and those skilled in the art can choose according to actual conditions.
[0062] Preferably, in step (3), the pickling temperature is 20-110°C, preferably 60-90°C; the time is 0.1-48h, preferably 4-12h.
[0063] According to the present invention, in step (3), there is no particular limitation on the solid-liquid separation method, and the solid-liquid separation can be carried out by a solid-liquid separation method known in the art, for example, solid-liquid separation can be carried out by filtration, suction filtration, centrifugation, etc. The liquid obtained after solid-liquid separation can be reused as a raw material for preparing nitrogen-oxygen co-doped carbon nanocages.
[0064] Preferably, in step (3), the washing is used to remove the acid wash agent remaining on the nano-carbon material, and therefore, various water washing methods that can wash the nitrogen-oxygen co-doped carbon nanocage to neutrality are applicable to the present invention. The drying is used to remove water on the nitrogen-oxygen co-doped carbon nanocage. Drying can be carried out by normal pressure drying or reduced pressure drying, and the drying conditions can adopt any feasible existing technology, preferably, drying is carried out at 80-140°C.
[0065] In the present invention, the metal oxide is introduced by the vacuum-filling method without introducing an exogenous template, which is conducive to large-scale production and has low cost.
[0066] According to the present invention, preferably, in step (4), the vacuum condition includes: an absolute pressure not higher than 10Pa, preferably 0-5Pa.
[0067] The present invention has a wide range of selection for the specific type of the iron salt, which can be selected from soluble organic or inorganic salts of iron, for example, at least one of ferric nitrate, ferric chloride and ferric citrate ammonium, preferably ferric nitrate.
[0068] Preferably, the concentration of the iron salt solution is 0.05-0.5 mol / L, preferably 0.2-0.5 mol / L.
[0069] Preferably, the impregnation is carried out under stirring conditions, and the impregnation time is 0.5-5h.
[0070] According to some preferred embodiments of the present invention, the amount of the iron salt and the nitrogen-oxygen co-doped carbon nanocage is such that, as measured by X-ray photoelectron spectroscopy, the molar content of carbon in the composite material is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%; preferably, as measured by X-ray photoelectron spectroscopy, the molar content of carbon in the composite material is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5%.
[0071] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the impregnated product to solid-liquid separation, washing and drying, and then subjecting the heat treatment to the solid-liquid separation and washing to remove the residual iron salt solution on the surface of the carrier. The present invention has no particular limitation on the specific operation and conditions of the solid-liquid separation and washing, and the solid-liquid separation and washing can be carried out by conventional methods in the art. For example, the solid-liquid separation can be carried out by filtering. Preferably, the washing can use water and / or alcohol as a detergent.
[0072] According to the present invention, preferably, the drying is performed by freeze drying. Preferably, the freeze drying temperature is -40 to -10°C and the time is 12-48 hours.
[0073] According to some preferred embodiments of the present invention, the heat treatment is carried out under an inert atmosphere, and the conditions of the heat treatment include: a temperature of 300-600°C, preferably 300-400°C; a time of 2-6h, preferably 2-4h. The inert atmosphere has the same definition as in step (2), for example, it can be argon.
[0074] According to the present invention, in step (5), the passivation treatment conditions include: temperature of 20-40°C and time of 0.5-2h. The passivation treatment is beneficial to further improve the stability of the material and prevent the material from spontaneously igniting when it suddenly contacts with air when it is taken out.
[0075] In the present invention, the oxygen-containing atmosphere may be a mixed gas of oxygen and an inert gas, and the volume content of oxygen in the oxygen-containing atmosphere is 1-3%.
[0076] According to some preferred embodiments of the present invention, the preparation method further comprises: subjecting the product obtained by the passivation treatment to a second pickling and drying. The second pickling is used to remove iron oxides on the surface of the product of the passivation treatment. The specific operation process of the second pickling can adopt the existing technology known to those skilled in the art, and the present invention has no special limitation on this.
[0077] The second pickling can be carried out with an acid or an acid aqueous solution conventional in the art, and can be the same or different from the pickling agent in the pickling in step (2), as long as the iron oxide on the surface of the passivated product can be removed. Preferably, the second pickling is carried out with a nitric acid aqueous solution, and the concentration of the nitric acid aqueous solution is preferably 0.5-2 mol / L. The present invention does not particularly limit the amount of the pickling agent, as long as the above purpose can be achieved, and those skilled in the art can choose according to actual conditions.
[0078] The second pickling may be optionally repeated. Preferably, the second pickling is repeated 1-2 times.
[0079] Preferably, the drying conditions include: temperature of 60-120° C. and time of 8-24 h.
[0080] The third aspect of the present invention provides a metallic lithium negative electrode, which includes a current collector and an active layer composited on the current collector, and the active layer includes the metallic lithium negative electrode active material described in the first aspect or the metallic lithium negative electrode active material prepared by the preparation method described in the second aspect.
[0081] In the present invention, the metal lithium negative electrode can have a conventional composition and structure in the art, as long as it contains the metal lithium negative electrode active material. The present invention has no special restrictions on the material and shape of the current collector, for example, it can be selected from any conventional flat current collector in the art. Preferably, the material of the current collector is selected from at least one of copper, titanium, nickel, iron and cobalt.
[0082] According to some preferred embodiments of the present invention, the active layer further comprises a binder and an optional conductive agent. The present invention has a wide range of choices for the types of the binder and conductive agent, and those skilled in the art can select them as needed.
[0083] The binder can be selected from fluorine-containing resins and / or polyolefin compounds. Preferably, the binder is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), sodium carboxymethyl cellulose, polyvinyl alcohol, styrene-butadiene rubber emulsion and acrylonitrile copolymer aqueous dispersion, preferably polyvinylidene fluoride.
[0084] The conductive agent may be any conductive agent known to those skilled in the art. Preferably, the conductive agent is selected from at least one of conductive carbon black (Super-P), acetylene black, nickel powder, copper powder and conductive graphite, preferably conductive carbon black.
[0085] According to some preferred embodiments of the present invention, based on the total mass of the active layer, the content of the active material is 50-95wt%, preferably 70-95wt%; the content of the binder is 1-50wt%, preferably 2-20wt%; the content of the conductive agent is 0-10wt%, preferably 5-10wt%.
[0086] In the present invention, there is no particular limitation on the composite method, and it can be carried out by conventional operations in the art. For example, the active layer can be composited on the current collector by coating or calendering.
[0087] A fourth aspect of the present invention provides a metal lithium battery, wherein the metal lithium battery comprises the metal lithium negative electrode described in the third aspect.
[0088] In the present invention, there is no particular limitation on the specific structure and composition of the metal lithium battery, and any conventional assembly method in the art can be adopted. The metal lithium battery can be any one of a lithium sulfur battery, a lithium oxygen battery, a lithium iodine battery, a lithium selenium battery, a lithium tellurium battery, a lithium oxygen battery, and a lithium carbon dioxide battery.
[0089] The present invention will be described in detail below through examples.
[0090] The surface morphology of the material was characterized by high-resolution transmission electron microscopy (HRTEM). The model of the high-resolution transmission electron microscope used was JEM-2100 (JEOL Ltd.), and the test conditions of the high-resolution transmission electron microscope were: the acceleration voltage was 200 kV.
[0091] The composition and valence state changes of each element on the surface of the material were determined by X-ray photoelectron spectroscopy (XPS). The X-ray photoelectron spectroscopy analysis was carried out on an ESCALab250 X-ray photoelectron spectrometer equipped with Thermo Avantage V5.926 software from Thermo Scientific. The excitation source was monochromatic Al Kα X-ray with an energy of 1486.6 eV and a power of 150 W. The penetration energy used for narrow scanning was 30 eV. The basic vacuum during the analysis was 6.5×10 -10 The electron binding energy was calibrated with the C1s peak (284.3 eV) of elemental carbon. The data were processed on Thermo Avantage software, and the sensitivity factor method was used for quantitative analysis in the analysis module.
[0092] The growth of metallic lithium dendrites was characterized by scanning electron microscopy (SEM). The model of the scanning electron microscope used was Hitachi S-4800 cold field scanning emission electron microscope. The test conditions of the scanning electron microscope were: the powder sample was fixed on the sample stage for observation by conductive glue, and the acceleration voltage was 5kV.
[0093] The following preparation examples are used to illustrate the preparation of the Fe2O3-carbon composite material in the present invention.
[0094] Preparation Example 1
[0095] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.
[0096] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 350°C at a rate of 5°C / min. After keeping the temperature constant for 2 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.
[0097] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 0.5M hydrochloric acid and stirred at 90°C for 4 hours for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of the nitrogen-oxygen co-doped carbon nanocages was 480 m 2 / g, and the pore volume of the cage wall is 0.77cm 3 / g.
[0098] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask, connect a 250mL dropping funnel, add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel; connect a piston joint for vacuuming to the other port of the two-necked flask, and connect a vacuum pump. Evacuate the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid, and place the filter cake in a freeze dryer at -10℃ and dry for 24h. Grind the dried sample and place it in a tubular furnace, calcine at 350℃ for 2h in an argon gas flow of 500mL / min, and cool to room temperature.
[0099] (5) At room temperature, the product obtained in step (4) was passivated in a 1 vol% O2 / Ar atmosphere for 0.5 h.
[0100] (6) The product obtained in step (5) was added into a 250 mL beaker, and 80 mL of 0.5 mol / L dilute nitric acid was added for washing. The washing with dilute nitric acid was repeated once to remove excess iron oxide particles on the surface, and then washed with deionized water until neutral. The product was placed in a forced air drying oven at 80 ° C for 2 h. The obtained Fe2O3-carbon composite material was recorded as A1.
[0101] The TEM image of this material is shown in Figure 1 As shown, it can be seen that the material contains many carbon cage units containing Fe2O3, each unit is in the shape of a hollow cage, and clear Fe2O3 lattice stripes can be seen in the cage, indicating that Fe2O3 is contained in the cage. At the same time, it can be obtained from the TEM image measurement that the particle diameter of the Fe2O3-carbon composite material A1 is about 5-20nm, the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 2nm, and the carbon cage has obvious graphite carbon lattice stripes.
[0102] The XPS image of Fe2O3-carbon composite material A1 is shown in Figure 2 As shown in the figure, it can be seen that in addition to carbon, the material also contains oxygen, nitrogen and iron. The atomic percentage of each element is: carbon is 91.56%, oxygen is 6.21%, nitrogen is 0.78%, and iron is 1.45%. The molar ratio of oxygen to nitrogen is 8:1.
[0103] The XPS spectrum of Fe 2p obtained by peak separation software is as follows: Figure 3 As shown, it can be seen that the iron element mainly exists in the form of Fe2O3.
[0104] Preparation Example 2
[0105] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.
[0106] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 400°C at a rate of 8°C / min. After maintaining the constant temperature for 3 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.
[0107] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 1.5M hydrochloric acid and stirred at 60°C for 8h for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6h to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of the nitrogen-oxygen co-doped carbon nanocages was 450m 2 / g, and the pore volume of the cage wall is 0.76cm 3 / g.
[0108] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask. Connect a 250mL dropping funnel and add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel. Connect a piston joint for vacuuming to the other port of the two-necked flask and connect it to a vacuum pump. Vacuum the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid and dry the filter cake in a freeze dryer at -10℃ for 24h. Grind the dried sample and place it in a tubular furnace. Calcined at 400℃ for 3h in an argon gas flow of 500mL / min and cooled to room temperature.
[0109] (5) The product obtained in step (4) was passivated with 1 vol% O2 / Ar for 0.5 h to obtain a Fe2O3-carbon composite material, which was recorded as A2. The morphology of the Fe2O3-carbon composite material A2 was characterized by TEM. Figure 1 Similarly, the particles are in the shape of hollow cages, and clear Fe2O3 lattice fringes can be seen inside the cages, indicating that Fe2O3 is contained in the cages. At the same time, the TEM image shows that the particle diameter of Fe2O3-carbon composite material A2 is about 5-20nm, and the thickness of the cage wall of nitrogen-oxygen co-doped carbon nanocage is 1.6nm.
[0110] XPS measured the atomic percentage of each element in the Fe2O3-carbon composite material as follows: carbon element is 92.71%, oxygen element is 5.32%, nitrogen element is 0.82%, iron element is 1.15%, and the molar ratio of oxygen to nitrogen is 6.5:1.
[0111] Preparation Example 3
[0112] (1) Weigh 14.67 g of basic nickel carbonate and 20.46 g of ethylenediaminetetraacetic acid (EDTA), add them into a beaker containing 100 mL of deionized water, stir at 80° C. to obtain a homogeneous solution, and continue heating and evaporating to obtain a solid precursor.
[0113] (2) placing the precursor obtained in step (1) in a porcelain boat, and then placing the porcelain boat in the constant temperature zone of a tubular furnace for low-temperature pyrolysis, introducing nitrogen at a flow rate of 80 mL / min, and heating to 650°C at a rate of 10°C / min. After keeping the temperature constant for 2 hours, stopping heating, and cooling to room temperature under a nitrogen atmosphere to obtain a pyrolysis product.
[0114] (3) The pyrolysis product obtained in step (2) was added to an aqueous solution containing 1M hydrochloric acid and stirred at 90°C for 4 hours for acid washing, then filtered, washed with deionized water until the filtrate was neutral, and then the filter cake was dried in a constant temperature oven at 120°C for 6 hours to obtain nitrogen-oxygen co-doped carbon nanocages. The specific surface area of the nitrogen-oxygen co-doped carbon nanocages was 348 m 2 / g, and the pore volume of the cage wall is 0.82cm 3 / g.
[0115] (4) Weigh 2g of carbon nanocages and add them to a two-necked flask, connect a 250mL dropping funnel, add 80mL of 0.5mol / L ferric nitrate aqueous solution to the dropping funnel; connect a piston joint for vacuuming to the other port of the two-necked flask, and connect a vacuum pump. Evacuate the two-necked flask to below 10Pa, close the piston joint, open the dropping funnel, and quickly add the ferric nitrate solution to the two-necked flask. After stirring for 2h, filter the mixed liquid and put the filter cake into a freeze dryer at -10℃ and dry for 24h. Grind the dried sample and put it into a tubular furnace, calcine it at 350℃ for 2h in an argon gas flow of 500mL / min, and cool it to room temperature.
[0116] (5) The product obtained in step (4) was passivated with 1% O2 / Ar for 0.5 h to obtain a composite material denoted as A3. At the same time, it can be obtained from TEM images that the particle diameter of the composite material A2 is about 5-20 nm, and the thickness of the cage wall of the nitrogen-oxygen co-doped carbon nanocage is 1.5 nm.
[0117] (6) The calcined sample was added into a 250 mL beaker and washed with 80 mL of 0.5 mol / L dilute nitric acid. The sample was washed with dilute nitric acid once to remove excess iron oxide particles on the surface. The sample was then washed with deionized water until neutral and dried in a forced air drying oven at 80 °C for 2 h. The obtained composite material was recorded as A3.
[0118] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 95.2%, oxygen element is 2.65%, nitrogen element is 0.95%, iron element is 1.2%, and the molar ratio of oxygen to nitrogen is 2.8:1.
[0119] Preparation Example 4
[0120] The method of Example 1 is followed, except that the concentration of the ferric nitrate aqueous solution is 5 mol / L.
[0121] The obtained composite material was recorded as A4.
[0122] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 87.33%, oxygen element is 5.92%, nitrogen element is 0.73%, iron element is 6.02%, and the molar ratio of oxygen to nitrogen is 8.1:1.
[0123] Comparative Preparation Example 1
[0124] The method of Example 1 is followed, except that step (4) is as follows: weigh 0.14 g of ferric citrate ammonium and dissolve it in 10 mL of aqueous solution. Slowly add 0.3 g of carbon nanocages into 10 mL of deionized water, fully disperse, mix with the solution of ferric citrate ammonium, soak for 6 hours, pour the mixture into a PTFE beaker, and blow dry at 80°C for 10 hours. The dried sample is placed in a tubular furnace protected by Ar atmosphere, the tubular furnace is evacuated for 5 minutes, filled with Ar gas, and the evacuation and filling are repeated three times to remove the air in the tubular furnace. In an Ar gas flow of 60 mL / min, the temperature is raised to 350°C at a heating rate of 10°C / min, and then the mixture is kept at a constant temperature for 2 hours, and then naturally cooled to room temperature.
[0125] Then, the passivation treatment was performed according to the method of Example 1, and the obtained product was recorded as composite material DA1.
[0126] XPS measured the atomic percentage of each element in the composite material as follows: carbon element is 91.97%, oxygen element is 6.23%, nitrogen element is 0.76%, and iron element is 1.04%. The molar ratio of oxygen to nitrogen is 8.2:1. TEM characterization showed that the ferric oxide in the composite material was loaded on the surface of the carbon cage and did not enter the carbon cage.
[0127] Comparative Preparation Example 2
[0128] A nitrogen-doped carbon-coated iron oxide negative electrode material Fe2O3@C was prepared according to the method of Example 1 of CN106816595A, and was denoted as composite material DA2. Characterization by SEM and TEM showed that the thickness of the nitrogen-doped carbon layer of the composite material was about 30 nm.
[0129] The following examples are used to illustrate the preparation of the metal lithium negative electrode active material in the present invention.
[0130] Example 1
[0131] Metal lithium is deposited into the Fe2O3-carbon composite material A1 by constant direct current deposition, and the specific method includes:
[0132] S1. Grind the iron oxide-nitrogen oxide co-doped carbon nanocage and the conductive agent Super-P in a mortar for 15 minutes. After grinding evenly, add the NMP solution of the binder PVDF (mass fraction 5%) in proportion. The mass ratio of the iron oxide-nitrogen oxide co-doped carbon nanocage, the conductive agent and the binder is 8:1:1. Stir on a magnetic stirrer for 6 hours; evenly apply the obtained paste slurry on a 9μm thick current collector copper foil with a coating thickness of 75μm; then dry it in a vacuum drying oven at 60℃ for 20 hours for use. The dried electrodes are respectively made into circular pole pieces with a diameter of 12mm; and maintained at a pressure of 8MPa for 30-180 seconds.
[0133] S2. Use the electrode sheet prepared as above as positive electrode, metallic lithium as negative electrode, Celgard membrane as separator, select 1 mol / L lithium bis(trifluoromethylsulfonate)imide as electrolyte, 1% lithium nitrate as additive, solvent volume ratio DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1, and assemble into CR2032 button battery.
[0134] S3, using the LAND CT2001A charge and discharge instrument of Wuhan Lanbo Electronics Co., Ltd. to perform constant DC deposition, the conditions include: at a constant current of 1mA / cm 2 Discharge for 4 hours under the conditions.
[0135] The battery is then disassembled in a glove box to obtain a negative electrode sheet S1 containing a metallic lithium negative electrode active material for standby use. The amount of metallic lithium deposited is calculated by weighing the mass of the electrode sheet before the deposition of metallic lithium and the mass of the electrode sheet after the deposition of metallic lithium. The content of metallic lithium is 10wt% based on the total amount of the metallic lithium negative electrode active material.
[0136] Example 2
[0137] Metal lithium is deposited into the Fe2O3-carbon composite material A2 by constant direct current deposition, and the specific method includes:
[0138] S1. Grind the iron oxide-nitrogen oxide co-doped carbon nanocage and the conductive agent Super-P in a mortar for 15 minutes. After grinding evenly, add the NMP solution of the binder PVDF (mass fraction 5%) in proportion. The mass ratio of the iron oxide-nitrogen oxide co-doped carbon nanocage, the conductive agent and the binder is 8:1:1. Stir on a magnetic stirrer for 6 hours; evenly apply the obtained paste slurry on a 9μm thick current collector copper foil with a coating thickness of 75μm; then dry it in a vacuum drying oven at 60℃ for 20 hours for use. The dried electrodes are respectively made into circular pole pieces with a diameter of 12mm; and maintained at a pressure of 8MPa for 30-180 seconds.
[0139] S2. Use the electrode sheet prepared as above as positive electrode, metallic lithium as negative electrode, Celgard membrane as separator, select 1 mol / L lithium bis(trifluoromethylsulfonate)imide as electrolyte, 1% lithium nitrate as additive, solvent volume ratio DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1, and assemble into CR2032 button battery.
[0140] S3, using the LAND CT2001A charge and discharge instrument of Wuhan Lanbo Electronics Co., Ltd. to perform constant DC deposition, the conditions include: at a constant current of 1mA / cm 2 Discharge for 10 hours under the conditions.
[0141] The battery is then disassembled in a glove box to obtain a negative electrode sheet S2 containing a metallic lithium negative electrode active material for standby use. The amount of metallic lithium deposited is calculated by weighing the mass of the electrode sheet before the deposition of metallic lithium and the mass of the electrode sheet after the deposition of metallic lithium. Based on the total amount of the metallic lithium negative electrode active material, the content of metallic lithium is 30wt%.
[0142] Example 3
[0143] The method of Example 1 is followed, except that Fe2O3-carbon composite material A3 is used to replace A1. The obtained negative electrode sheet is recorded as S3.
[0144] Example 4
[0145] The method of Example 1 is followed, except that Fe2O3-carbon composite material A4 is used to replace A1. The obtained negative electrode sheet is denoted as S4.
[0146] Example 5
[0147] The method of Example 1 is different from that of the constant direct current deposition conditions, which include: 2 The battery was discharged for 2 hours under the conditions, and then the battery was disassembled in a glove box to obtain a negative electrode sheet S5 containing a metallic lithium negative electrode active material for use. By weighing the mass of the electrode sheet before the deposition of metallic lithium and the mass of the electrode sheet after the deposition of metallic lithium, the content of metallic lithium was 5wt% based on the total amount of the metallic lithium negative electrode active material.
[0148] Comparative Example 1
[0149] The method of Example 1 is followed, except that DA1 is used to replace A1. The obtained negative electrode sheet is denoted as DS1.
[0150] Comparative Example 2
[0151] The method of Example 1 was followed, except that DA2 was used to replace A1. The obtained negative electrode sheet was denoted as DS2.
[0152] Test Case
[0153] The negative electrode sheet containing negative electrode active materials obtained in the above embodiments and comparative examples was used as a metal lithium negative electrode. In the metal lithium negative electrode, based on the total weight of the active layer, the content of the metal lithium negative electrode active material was 80.16% by weight, the content of the binder PVDF was 9.92% by weight, and the content of the conductive agent Super-P was 9.92% by weight. Metal lithium was used as a counter electrode, Celgard membrane was used as a diaphragm, 1 mol / L lithium bis(trifluoromethylsulfonic acid)imide was selected as an electrolyte, 1% lithium nitrate was selected as an additive, and the solvent volume ratio DOL (1,3-dioxolane): DME (ethylene glycol dimethyl ether) = 1:1 was assembled into a CR2032 button battery.
[0154] The battery was tested with a constant current charge and discharge tester using the LAND CT2001A from Wuhan Rambo Electronics Co., Ltd. at 25°C and a constant current of 1 mA / cm 2 Under the conditions of charge and discharge for 1h each (one charge and discharge process is one cycle), and the above charge and discharge process is repeated, and the cycle is kept at a stable overpotential. When the overpotential during the charge or discharge process increases by 50% or more than the overpotential in the previous cycle, the cycle is ended and the cycle time is recorded. The results are shown in Table 1.
[0155] Table 1
[0156]
[0157] The cycled battery was disassembled, the negative electrode was taken out, the lithium salt and lithium nitrate on the surface of the electrode were cleaned with DME, and the lithium deposition morphology was observed by SEM test. The SEM test results of Example 1 are as follows: Figure 4 As shown, the deposition of metallic lithium is relatively uniform and flat, indicating that the negative electrode active material provided by the present invention is conducive to uniform lithium deposition. However, the lithium deposition morphology on the surface of the negative electrode plate disassembled in Comparative Example 1 has obvious dendrite formation.
[0158] It can be seen from the results in Table 1 that the metal lithium negative electrode active material provided by the present invention has a high specific capacity, still has a high coulombic efficiency after 50 cycles, and has good cycle stability.
[0159] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A metallic lithium negative electrode active material, characterized in that: The negative electrode active material includes metallic lithium and Fe2O3-carbon composite material; Wherein, the Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages; The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
2. The negative electrode active material according to claim 1, wherein The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 84-94%, the molar content of oxygen is 5-8%, the molar content of nitrogen is 0.5-3%, and the molar content of iron is 0.5-5%; Preferably, in the Fe2O3-carbon composite material, the molar ratio of oxygen to nitrogen is 5-15:1, preferably 5-10:
1.
3. The negative electrode active material according to claim 1 or 2, wherein Based on the total amount of the negative electrode active material, the content of metallic lithium is 5-50wt%, preferably 10-30wt%, and the content of the Fe2O3-carbon composite material is 50-95wt%, preferably 70-90wt%; Preferably, the metallic lithium is filled in the cage cavity of the nitrogen and oxygen co-doped carbon nanocage.
4. The negative electrode active material according to any one of claims 1 to 3, wherein The particle diameter of the Fe2O3-carbon composite material is 5-40nm, preferably 5-30nm, more preferably 5-20nm; And / or, the thickness of the cage wall of the nitrogen and oxygen co-doped carbon nanocage in the Fe2O3-carbon composite material is 1-30 nm, preferably 1-10 nm, and more preferably 1-5 nm.
5. The negative electrode active material according to any one of claims 1 to 4, wherein: The specific surface area of the nitrogen and oxygen co-doped carbon nanocage is 50-1000m 2 / g, preferably 200-800m 2 / g, more preferably 300-600m 2 / g; And / or, the pore volume of the cage wall of the nitrogen and oxygen co-doped carbon nanotubes is 0.5-1cm 3 / g, preferably 0.65-1cm 3 / g.
6. A method for preparing a metallic lithium negative electrode active material, the preparation method comprising: Depositing metallic lithium into the Fe2O3-carbon composite material by electrodeposition; The Fe2O3-carbon composite material comprises nitrogen-oxygen co-doped carbon nanocages and Fe2O3 nanoparticles filled in the nitrogen-oxygen co-doped carbon nanocages; The molar content of carbon in the Fe2O3-carbon composite material measured by X-ray photoelectron spectroscopy is 75-98%, the molar content of oxygen is 1-10%, the molar content of nitrogen is 0.5-5%, and the molar content of iron is 0.5-10%.
7. The preparation method according to claim 6, wherein: The preparation method of the Fe2O3-carbon composite material comprises: (1) providing a homogeneous solution containing a transition metal salt, a nitrogen-containing organic carboxylic acid and a solvent, and then removing the solvent from the homogeneous solution to obtain a precursor; the nitrogen-containing organic carboxylic acid is ethylenediaminetetraacetic acid; and the mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.1-100; (2) subjecting the precursor to low-temperature pyrolysis in an inert atmosphere and / or a reducing atmosphere to obtain a pyrolysis product; the temperature of the low-temperature pyrolysis is not higher than 650° C.; (3) acid-washing the pyrolysis product, and then performing solid-liquid separation, washing and drying to obtain nitrogen-oxygen co-doped carbon nanocages; (4) impregnating the nitrogen-oxygen co-doped carbon nanocage with an iron salt solution under vacuum conditions, and then performing a heat treatment; (5) Under an oxygen-containing atmosphere, the product obtained in step (4) is passivated to obtain a Fe2O3-carbon composite material.
8. The preparation method according to claim 7, wherein: The mass ratio of the transition metal salt to the nitrogen-containing organic carboxylic acid is 1:0.5-50, preferably 1:0.5-5; And / or, the transition metal salt is selected from organic acid salts and / or inorganic salts of transition metals; preferably, the organic acid salt of transition metals is an organic carboxylate salt containing no heteroatoms, preferably an acetate; preferably, the inorganic salt of transition metals is at least one of transition metal halides, carbonates and basic carbonates; and / or, the transition metal is a Group VIII metal and / or a Group IB metal, preferably at least one of iron, cobalt, nickel and copper, more preferably nickel; And / or, the solvent is ethanol and / or water.
9. The preparation method according to claim 7 or 8, wherein: In step (2), the low-temperature pyrolysis conditions include: a heating rate of 0.5-30°C / min, preferably 1-10°C / min; a temperature of 350-450°C, preferably 350-400°C; a constant temperature time of 20-600min, preferably 60-480min; and / or, the inert atmosphere is provided by at least one of nitrogen, argon, neon and helium; And / or, the reducing atmosphere is hydrogen.
10. The preparation method according to any one of claims 7 to 9, wherein: In step (3), the acid washing removes the transition metals in the pyrolysis product to form a hollow cage-like structure; Preferably, the pickling agent used for pickling the pyrolysis product is an inorganic acid aqueous solution and / or an organic acid aqueous solution, preferably at least one of a hydrochloric acid aqueous solution, a sulfuric acid aqueous solution, a nitric acid aqueous solution and a citric acid aqueous solution, more preferably a hydrochloric acid aqueous solution; And / or, the concentration of the inorganic acid aqueous solution or the organic acid aqueous solution is 0.5-2 mol / L; And / or, in step (3), the pickling temperature is 20-110°C, preferably 60-90°C; the time is 0.1-48h, preferably 4-12h.
11. The preparation method according to any one of claims 7 to 10, wherein: In step (4), the vacuum conditions include: an absolute pressure not higher than 10 Pa; And / or, the concentration of the iron salt solution is 0.05-0.5 mol / L; And / or, the iron salt is at least one of ferric nitrate, ferric chloride and ferric ammonium citrate; And / or, the heat treatment is carried out under an inert atmosphere, and the conditions of the heat treatment include: a temperature of 300-600° C. and a time of 2-4 h; And / or, in step (5), the passivation treatment conditions include: temperature of 20-30°C, time of 0.5-2h; Preferably, the volume content of oxygen in the oxygen-containing atmosphere is 1-3%.
12. The preparation method according to any one of claims 6 to 11, wherein: The electrodeposition is selected from constant direct current electrodeposition and / or pulse electrodeposition; Preferably, the electrodeposition is a constant direct current electrodeposition, and the current of the constant direct current electrodeposition can be 0.5-5 mA / cm 2 ; Preferably, the electrodeposition is such that, based on the total amount of the negative electrode active material obtained, the content of metallic lithium is 5-50wt%, preferably 10-30wt%, and the content of the Fe2O3-carbon composite material is 50-95wt%, preferably 70-90wt%.
13. A metallic lithium negative electrode, characterized in that: The metal lithium negative electrode comprises a current collector and an active layer composited on the current collector, wherein the active layer comprises the metal lithium negative electrode active material according to any one of claims 1 to 5 or the metal lithium negative electrode active material prepared by the preparation method according to any one of claims 6 to 12.
14. A metal lithium battery, characterized in that: The metal lithium battery comprises the metal lithium negative electrode as claimed in claim 13.
Citation Information
Patent Citations
Nitrogen-oxygen co-doped carbon-coated metal lithium anode active material, anode, lithium metal battery and preparation and application thereof
CN111755668A
Metal oxide composite material and preparation method and application thereof
CN113540456A
Negative electrode material, negative electrode sheet, electrochemical device, and electronic device
CN114270574A
Nitrogen-doped nano carbon material and preparation method thereof, metal lithium negative electrode and preparation method thereof, and metal lithium battery
CN116031405A